Are only-children difficult team members?. Issue 47 (8th October 2021) - Yang, Fanzheng; Weng, Weiwei
ABSTRACT: The ever-increasingly complex economic activities across all industries have rendered teamwork a ubiquitous feature of the modern economy. Selecting the right employees, however, is conceived to be an ever more challenging task in the presence of an increasing number of adult only- children, who are widely perceived to be spoilt, self-centred and thus with weak team spirit. Our experimental study reassesses such negative stereotype by investigating only children's participation willingness and their commitment to a group effort. Only children are found to contribute as much as their counterparts with siblings to the group effort although with slightly weaker willingness to join. Furthermore, the provision of peer information about relative performance is found to be significantly more effective in incentivizing only children than non-only children on both their willingness to participate in teamwork and their contribution to a group effort. Together, our findings suggest that only children can outperform their counterparts with siblings in teamwork as the uncertainty of team productivity is reduced by the introduction of feedback information.